Senegal Economic Update, April 2018 : Recent Growth Drivers in Senegal, and the Role of Agriculture in Developing a Resilient and Inclusive Economy - World Bank (World Bank, Washington, DC, 2018)
The Economic Update (SEU) evaluates the recent (2016-17) growth performance and macroeconomic policies in Senegal, thus providing a basis for the policy dialog with the Government and other stakeholders. The first section of the Economic Update evaluates the drivers of growth and the macroeconomic framework. Three-year perspectives are also included, underlining risks and challenges. The second section evaluates the agricultural sector in more detail focusing on the recent evolution of the agriculture sector and on the impact of public sector involvement